Modified Pulse Shapes for Effective Neural Stimulation - Hofmann, Lorenz; Ebert, Martin; Tass, Peter A.; Hauptmann, Christian (Frontiers in Neuroengineering, 2011)
Electrical stimulation of neuronal structures is used as treatment of many neu- rological disorders, e.g. for the treatment of Parkinsons disease via deep brain stimulation. To reduce side effects, to avoid tissue or electrode damage and to increase battery lifetimes, an effective but gentle electrical stimulation is of prime importance. We study different modified pulse shapes for application in deep brain stimulation with respect to their efficiency to initiate neuronal activity. Numeri- cal simulations of two mathematical neuron models are performed to investigate the effectiveness of different modified pulse shapes. According to our results, the considered pulse shapes show a considerably increased efficiency in terms of both activation and entrainment of neural activity. We find that the introduction of a gap of specific and optimized duration in a biphasic pulse and the reversal of the stan- dard pulse phase order yield stimulation protocols that may increase the efficiency and therefore reduce the energy consumption of stimulation. The improvements are achieved only by simple modifications of existing stimulation techniques. The modification of the pulse shapes results in an improvement of up to 50% for both the activation of resting neurons and the entrainment of bursting neurons.